2020
DOI: 10.1101/2020.03.23.002865
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Screening for functional circular RNAs using the CRISPR-Cas13 system

Abstract: Circular RNAs (circRNAs) produced from back-spliced exons are widely expressed, but individual circRNA functions remain poorly understood due to inadequate methods, such as RNAi and genome engineering, in distinguishing overlapped exons in circRNAs from those in linear cognate mRNAs 1,2 . Here we report that the programable RNA-guided, RNA-targeting CRISPR-Cas13, RfxCas13d, effectively and specifically discriminates circRNAs from mRNAs, using guide (g)RNAs targeting sequences spanning the back-splicing junctio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 44 publications
3
38
0
Order By: Relevance
“…Recently, the novel CRISPR/Cas13-based approaches using guide RNAs, which target the circRNA-specific back-splicing junction sites, have been used to achieve precise and robust circRNA silencing without disturbing their linear cognate mRNAs [67,68]. These studies suggest that the application of CRISPR/Cas-based circRNA engineering systems may be a promising method for performing functional studies of circRNA in human cancers.…”
Section: Methods For Detecting and Characterizing Circrnasmentioning
confidence: 99%
“…Recently, the novel CRISPR/Cas13-based approaches using guide RNAs, which target the circRNA-specific back-splicing junction sites, have been used to achieve precise and robust circRNA silencing without disturbing their linear cognate mRNAs [67,68]. These studies suggest that the application of CRISPR/Cas-based circRNA engineering systems may be a promising method for performing functional studies of circRNA in human cancers.…”
Section: Methods For Detecting and Characterizing Circrnasmentioning
confidence: 99%
“…The Cas13 family is unified by the presence of two conserved HEPN ribonuclease motifs and a common RNA cleavage mechanism, yet divided into several subtypes on the basis of sequence diversity and coding sequence length. Cas13d enzymes, in particular the engineered Cas13d-NLS from R. flavefaciens strain XPD3002 (CasRx) (Konermann et al, 2018), are highly compact RNA targeting effectors with robust activity in mammalian and plant cells relative to other subtypes (Wessels et al, 2020;Li et al, 2021;Mahas et al, 2019), motivating their further development as RNA targeting tools.…”
Section: Introductionmentioning
confidence: 99%
“…In all cases, shRNAs, siRNAs, or gRNAs were designed to target sequences of circRNAfeatured BSJ sites for targeted circRNA repression. Comparative analyses suggested that circRNA knockdown by RfxCas13 showed much less off-target on cognate mRNAs than those by shRNAs/siRNAs [56]. Although nearly all BSJs are targetable by RfxCas13-gRNA, the execution at the RNA level of circRNA LOF depends on the continuous expression of the RfxCas13 system in cells.…”
Section: Discussionmentioning
confidence: 97%
“…5), in human 293FT and HCT116 cell lines. Other than KO, reducing circRNA expression was also reported at the RNA level by short hairpin RNAs (shRNAs), small interfering RNAs [26,27], or RNA-targeting type VI CRISPR effector RfxCas13 systems [56]. In all cases, shRNAs, siRNAs, or gRNAs were designed to target sequences of circRNAfeatured BSJ sites for targeted circRNA repression.…”
Section: Discussionmentioning
confidence: 99%